A queer deviance in Turkish detective fiction:|The Hop-Çiki-Yaya series by Mehmet Murat Somer - Yüce, Cüneyt. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Detective fiction has often been labeled as the “stepchild of literature” or “cheap literature” by literary critics and it also has been looked down on by being considered as an “escapist fiction”. However, funnily enough, it is one of the most strictly prescribed genres of literature. As it has usually been stated, detective fiction, which is one of the entertainment tools of modern mass society, provides readers to be a part of conformity. And this conformity is based on white middle-class men’s morals. In this study, detective fiction genre, which takes its shape around masculinist conventions, is analyzed around institution and class-implying concepts such as genre and gender. In order to analyze these concepts, Mehmet Murat Somer’s Hop-Çiki-Yaya series, of which protagonist is a transvestite, has been chosen as primary fictional texts. Here, it is advocated that, our perception of gender and genre has been built through some certain repetitions; therefore, based on Judith Butler’s conceptualization, these two concepts are presented as performative and fluid becomings. On the other hand, it has been shown that, both the series and its protagonist are ultimately parts of certain borders. Not only queer notions and their intersections with detective fiction genre but also all of their reflections in Somer’s series have been chosen as the focal point of this research.
Keywords: Detective and mystery stories, Turkish.